Quasi-90-day oscillation observed in the MLT region at low latitudes from the Kunming meteor radar and SABER - Wen Yi; XiangHui Xue; JinSong Chen; TingDi Chen; Na Li (Earth and Planetary Physics, 2019)
Observations of a quasi-90-day oscillation in the mesosphere and lower thermosphere (MLT) region from April 2011 to December 2014 are presented in this study. There is clear evidence of a quasi-90-day oscillation in temperatures obtained from the Kunming meteor radar (25.6°N, 103.8°E) and Sounding of the Atmosphere using Broadband Emission Radiometry (SABER), as well as in wind observed by the Kunming meteor radar. The quasi-90-day oscillation appears to be a prominent feature in the temperatures and meridional wind tides and presents quite regular cycles that occur approximately twice per year. The amplitudes and phases of the quasi-90-day oscillation in the SABER temperature show a feature similar to that of upward-propagated diurnal tides, which have a vertical wavelength of ~20 km above 70 km. In the lower atmosphere, a similar 90-day variability is presented in the surface latent heat flux and correlates with the temperature in the MLT region. Similar to the quasi-90-day oscillation in temperature, a 90-day variability of ozone (O3) is also present in the MLT region and is considered to be driven by a similar variability in the upwardly-propagated diurnal tides generated in the lower atmosphere. Moreover, the 90-day variability in the absorption of ultraviolet (UV) radiation by daytime O3 in the MLT region is an in situ source of the quasi-90-day oscillation in the MLT temperature.